(untitled) (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
The expanding development of digital micro-entrepreneurship has opened new opportunities for underserved communities to participate in technology based economic activities. However, disparities in digital access, low technological literacy, and limited ecosystem support remain major barriers for marginalized groups in leveraging digital economic opportunities. This study aims to examine in depth how digital micro-entrepreneurship programs can promote inclusive economic growth, strengthen the entrepreneurial capacity of low income communities, and create more equitable economic opportunities. The research method employed is a qualitative approach through in-depth interviews with program participants, field observations of digital entrepreneurial activities, and analysis of training documents and program reports to understand the empowerment processes that emerge. The findings indicate that digital micro-entrepreneurship programs are able to enhance digital literacy, platform based marketing skills, and confidence in running a business, particularly for women and youth in underserved areas. Additionally, the results show an increase in market connectivity, income diversification, and the creation of collaborative networks among micro-entrepreneurs, which strengthens the economic resilience of the community. This study concludes that digital-based micro-entrepreneurship empowerment is an effective strategy for fostering inclusive growth, provided that there is continuous mentoring, adequate digital infrastructure, and program integration with the local social context so that digital economic transformation can take place sustainably and equitably.